Features of qualification of corpus delicti in violation of environmental requirements for economic or other activities - Aitimov, B.Zh.; Seriev, B.A.; Bekezhanov, D.N. (Bulletin of the Karaganda University “Law Series”, 2021)
The article examines the features of qualification of corpus delicti in violation of environmental requirements for economic or other activities as one of the types of environmental criminal offenses. This crime is very rare in practice, which is evident from the lack of judicial practice depending on the nature of the crime. There are many reasons for this. One of the main reasons is the lack of theoretical studies that allow recognizing the composition of a socially dangerous act as a crime considered by Article 324 of the Criminal Code of the Republic of Kazakhstan, as well as insufficient competence of representatives of the bodies investigating these criminal acts. The purpose of the study is to determine the characteristics and difficulties in qualifying the crime considered in Article 324 of the Criminal Code of the Republic of Kazakhstan, and consider ways of solving it and ensuring its disclosure. The article notes that the main difficulty in qualifying the corpus delicti under Article 324 of the Criminal Code of the Republic of Kazakhstan is the determination of the object of the crime. In authors’ opinion its main reason is the blanketness of the norm. In committing this crime, the subject encroaches on environmental requirements for economic or other activities, which are considered in the Environmental Code of the Republic of Kazakhstan, as well as in land, water and other legislation regulating environmental protection. The article describes the corpus delicti using the methods of statistics, analysis and synthesis. As a result of the study the main points of qualification of corpus delicti in violation of environmental requirements for economic or other activities are considered.